Air quality alerts and don't drive appeals: evidence on voluntary pollution mitigation dynamics from Germany [data and replication package] - Dangel, Alexander; Goeschl, Timo (Universität, 2025)
This replication package provides data and Stata code to reproduce all results in "Air Quality Alerts and Don't Drive Appeals: Evidence on Voluntary Pollution Mitigation Dynamics from Germany" by Alexander Dangel and Timo Goeschl.
Gefördert durch: Deutsche Bundesstiftung Umwelt: 20020/672; Heidelberg Center for the Environment, Heidelberg University
Keywords: Forschungsdaten; Datenbank